Survey of N-Nitrosamine Contamination and Risk Assessment of N-Nitrosodimethylamine in Dried Aquatic Products - TANG Cuiying, CHEN Huafeng, HUANG Qishu, LI Jianwen, HUANG Siting CHEN Lijuan, FU Wusheng (Shipin Kexue)
Objective: This study investigated the levels of N-nitrosodimethylamine (NDMA) and eight other N-nitrosamines in dried aquatic products, with a primary focus on assessing the carcinogenic risk of NDMA due to its significant carcinogenicity and dominance among N-nitrosamine contaminants. Methods: Homogenized samples were subjected to steam distillation, and dichloromethane was used to absorb the distillate. Liquid-liquid extraction was employed to purify and separate the target analytes. The concentrated extract was then quantitatively analyzed using ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). Through three 24-hour dietary recalls, a total of 26 933 volunteers from across the country were surveyed about average daily intake of dried aquatic products. Based on the survey results, the carcinogenic risk of NDMA exposure was assessed by the margin of exposure (MoE) method. Results: The limit of detection (LOD) for NDMA was 0.3 μg/kg. At a spiked level of 2.0 μg/kg, the recoveries of NDMA ranged from 96.9% to 100.1%, with a relative standard deviation (RSD) of 1.56% (n = 4). The detection rate of NDMA in commercially available dried aquatic product samples was 77.8% (154/198), at concentrations ranging from 0.51 to 122 μg/kg with an average level of 5.23 μg/kg. Additionally, 28.8% of the samples exceeded the maximum allowable limit. The average intake of dried aquatic products among consumers of different age groups ranged from 4.05 to 32.43 g/d, with high consumption (P97.5) ranging from 16.67 to 66.67 g/d. Risk assessment indicated that the dietary exposure to NDMA in people of all age groups with average and high (P97.5) consumption levels of dried aquatic products were 0.46 and 3.65 ng/(kg mb·d), with MoE values of 6.1 × 104 and 7.7 × 103, respectively. Conclusion: The potential carcinogenic risk associated with NDMA intake from dried aquatic products is low for all respondents, and the same goes for average consumers across all age groups, who do not require any priority attention. However, NDMA intake poses a potential carcinogenic risk for heavy consumers (P97.5) across all age groups, who require priority attention.